The problem of syntactic ambivalence in corpus linguistics - Kida, Ireneusz (Lingua Posnaniensis, 2012)
The purpose of this article is to present a technique of dual annotation of Old English ambivalent structures in diachronic annotated corpus linguistics. In languages there are often structures which are ambivalent, and it is difficult to establish whether they are main or dependent. These clauses are problematic for a corpus linguist annotating them for computer analysis of word order configurations. As a solution to this problem we suggest that such structures be annotated in two ways, namely on the one hand as main and on the other hand as dependent. Such a procedure allows one to obtain more objective results from word order analysis. Moreover, dual annotation is more flexible and is able to grasp the changeable nature of language